Isolation, partial characterization and identification as potential biological agents of fungal isolates in some Colombian regions - IBARRA, ALBA MARY; VARELA-R., AMANDA (Revista Colombiana de Entomología, 2002)
We began a fungí culture collection isolated from different Colombian regions, for uses in education, research, and as potential biological agents. We collected 110 samples of vegetal material, dead insects and soil, from different vegetation communities, in the departments of Meta, Cauca, Cordoba, and Cundinamarca. The fungal isolates were treated in culture media of defined composition. We identified 58 isolates with biocontrol potential. Of all the isolates, 3,2% were primary entomopathogenic, 20,6% phytopathogen controllers, 28,6% secondary entomopathogens and 47,6% possessed no biocontrol potential. Most of the fungí were isolated in the Department of Cauca (67% of the total number). 38,7 were derived from soil, 28,6% from the plant material and 32, 7% from insects, fruits, and litterfall samples. The isolates were preserved in both soil and distilled water. Their macroscopic and microscopic morphological characteristics were evaluated 15, 45, and 90 days after collection. The preservation of distilled water was found to be the best method due to its low cost. ease of manipulation and recuperation of isolates. The isolates were evaluated in vitro against pesticides such as Furadan, Manzate, Malathion and Benlate al concentrations of 25 and 250 ppm. Manzate reduced the growth rate of all isolates significantly (p<0,01). With respect to the negative control, Furadan and Ben late inhibited the growth of all the isolates completely at both concentrations (p<0,01). This collection will serve as an important reference for future studies of these biological control agents (isolates) at molecular and physiological levels.